Luminescence properties of color-tunable YNbO4: Dy3+, Tm3+ phosphors. Issue 4 (1st October 2020) - Wang, Xin; Li, Xiangping; Xu, Sai; Cheng, Lihong; Sun, Jiashi; Zhang, Jinsu; Zhang, Xizhen; Chen, Baojiu
ABSTRACT: Usually, Dy 3+ doped phosphors can simultaneously generate both blue and yellow emissions which can be mixed as white light if the intensities of them are closer. The aim of this work is to explore white-light generation in Dy 3+ doped YNbO4 phosphors by introducing Tm 3+ to compensate the lack of blue component of Dy 3+ . To this end, the Dy 3+, Tm 3+ single- and co-doped YNbO4 phosphors were synthesized via a high-temperature solid-state reaction method. Under the excitation of 354 nm, the YNbO4 : Dy 3+ phosphors exhibit a blue emission at 487 nm and a yellow emission at 579 nm and the results indicated that the white light cannot be obtained from Dy 3+ single-doped YNbO4 phosphors owing to the deficiency of blue spectral component. To tune the emission color, Tm 3+ was introduced into Dy 3+ doped samples, and the energy transfer behavior between Tm 3+ and Dy 3+ was investigated based on the fluorescence dynamics. The chromatic property of the while light emitting phosphor was studied. High-quality white emission was obtained when Tm 3+ concentration was 1.0 mol%. The color coordinates and the correlated color temperature for the concentration-optimized sample are (0.3355, 0.3345) and 5352 K, respectively.